2020
DOI: 10.9734/cjast/2020/v39i3731086
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Processing and Fermentation on Functional Properties and on Anti-nutritional Factors in Horse Gram (Macrotyloma uniflorum)

Abstract: Aim: The study was conducted to understand the Effect of processing and fermentation on functional properties and on anti-nutritional factors in Horse Gram (Macrotyloma uniflorum). Place and Duration of Work: The study was carried out in Department of Agricultural Microbiology, GKVK, University of Agricultural Sciences, Bangalore during 2019-20. Methodology: Horse gram seeds were procured from National seed project, thoroughly cleaned and were subjected to different processing methods (soaking, roa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…However, the crude fiber, tannins, phytic acid, and other antinutritional factors contained in mulberry leaves affect the absorption and utilization of nutrients in animals [ 14 ]. Studies have found that the fermentation of silage could significantly reduce the contents of the crude fiber and antinutritional factors in mulberry leaves, minimize nutrient loss, and improve the palatability of mulberry leaves, which is the most commonly used processing method for livestock and poultry feed [ 15 , 16 ]. Microbial fermentation technology can transform the indigestible macromolecules in mulberry leaves into digestible small molecules, such as amino acids, small peptides, and organic acids, and can release their nutrients [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the crude fiber, tannins, phytic acid, and other antinutritional factors contained in mulberry leaves affect the absorption and utilization of nutrients in animals [ 14 ]. Studies have found that the fermentation of silage could significantly reduce the contents of the crude fiber and antinutritional factors in mulberry leaves, minimize nutrient loss, and improve the palatability of mulberry leaves, which is the most commonly used processing method for livestock and poultry feed [ 15 , 16 ]. Microbial fermentation technology can transform the indigestible macromolecules in mulberry leaves into digestible small molecules, such as amino acids, small peptides, and organic acids, and can release their nutrients [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…W hen compared to raw horse gram, iron, protein, calcium and phosphorus did not change significantly, however, tannins and phytates were found reduced during processing (Thirukkumar and Gurumeenakshi, 2015). According to (Sarvani et al, 2020), when processing and fermentation were combined anti-nutritional components were reduced more than when processing was used alone. Additionally, it was shown that flour that had been boiled…”
Section: Anti-nutritional Factorsmentioning
confidence: 99%
“…Consequently, fermentation effects are also influenced by food composition, as other food constituents such as fibers could reduce specific mineral availability. To overcome these difficulties, seed germination and incubation of foods with polyphenol oxidase or phytase (through fermentation) could help enhance the availability of minerals by decreasing the phytate or tannin levels [58,59]. During fermentation, pH is reduced, which enhances the absorption of iron because of ferric iron conversion to the more readily absorbed ferrous iron.…”
Section: Fermentation Affects Enzyme Activation To Improve the Nutritmentioning
confidence: 99%